The Impact of the Angular Head Movement’s Velocity during Diagnostic Maneuvers on Proper Benign Positional Paroxysmal Vertigo Diagnosis and Therapy - Igor Anurin; Marlena Ziemska-Gorczyca; Dana Pavlovschi; Ireneusz Kantor; Karolina Dżaman (Diagnostics, 2023)
Based on the current state of the BPPV field, there are no guidelines that specify an angular head movement’s velocity (AHMV) during diagnostic maneuvers of BPPV. The aim of this study was to evaluate the impact of AHMV during diagnostic maneuvers on proper BPPV diagnosis and therapy. The analysis covered the results obtained in 91 patients with a positive result of the Dix-Hallpike (D-H) maneuver or the roll test. The patients were divided into four groups based on values of AHMV (high 100–200°/s and low 40–70°/s) and the BPPV type (posterior: PC-BPPV or horizontal: HC-BPPV). The parameters of the obtained nystagmuses were analyzed and compared to AHMV. There was a significant negative correlation between AHMV and latency of nystagmus in all study groups. Furthermore, there was a significant positive correlation between AHMV and both maximum slow phase velocity and average frequency of nystagmus in the PC-BPPV groups, whereas it was not observed in the HC-BPPV patients. Complete relief of symptoms was reported after 2 weeks and was better in patients diagnosed with maneuvers performed with high AHMV. High AHMV during the D-H maneuver allows the nystagmus to be more visible, increasing the sensitivity of diagnostic tests and is crucial for a proper diagnosis and therapy.